Correlating Spirometric Parameters with Breath-Holding Time and Maximum Chest Expansion in Healthy Young Adults - Amatya, Mrigendra; Pun, D.B. (Nepal Medical College Journal, 2019)
The spirometric measurements are very sensitive, accurate and reliable parameters, which have diagnostic as well as prognostic values. We aimed to find the reliability of two simple measurements, namely chest expansion and voluntary breath holding, which are often suggested as tools for screening and monitoring of respiratory diseases. A cross-sectional descriptive study was conducted on students of Nepal Medical College. Measurements of spirometry (forced vital capacity, FVC in liter; forced expiratory volume in first second, FEV1 in liter; and peak expiratory flow rate, PEF in liter persecond), cirtometry (average of maximum chest expansion, CE in centimeter), and breath-holding time (maximum voluntary apnea at end-inspiration, MVAIT and maximum voluntary apnea at end expiration, MVAET in second) were performed. Degrees of correlation (Pearson’s r) were determined between different parameters; setting level of significance at 95%. Total 308 students (M=164, 53.25%;F=144, 46.75%) participated. Owing to very highly significant differences between males and females, gender-separate correlations were determined. In males, CE correlation was very highly significant (p=0.000) with FVC and FEV1 but not with PEF. MVAET correlated significantly with FVC, FEV1 and PEF; MVAIT correlation was not significant with any parameters. In females, CE correlation was significant with FVC and FEV1 but not with PEF; MVAET and MVAIT correlations were not significant with any of the parameters. In conclusion, the correlation of CE with different spirometric parameters is significant but not very strong (0.3<r<0.5). Also, gender differences exist. Therefore, using CE and breath-holding time may not be appropriate to assess respiratory ventilatory function.